2006
DOI: 10.1002/jcb.21142
|View full text |Cite
|
Sign up to set email alerts
|

Key developmental regulators change during hyperoxia‐induced injury and recovery in adult mouse lung

Abstract: Developmentally important genes have recently been linked to tissue regeneration and epithelial cell repair in neonatal and adult animals in several organs, including liver, skin, prostate, and musculature. We hypothesized that developmentally important genes play roles in lung injury repair in adult mice. Although there is considerable information known about these processes, the specific molecular pathways that mediate injury and regulate tissue repair are not fully elucidated. Using a hyperoxic injury model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
3
35
0
1
Order By: Relevance
“…Thyroid transcription factor 1 (TTF1), a key transcription factor in type II cell development, did not increase in hyperoxia (Fig. 4A), consistent with a previous report (14). Furthermore, C/EBP␣ siRNA injection did not change TTF1 mRNA levels in hyperoxia.…”
Section: Intrapulmonary Delivery Of C/ebp␣ Sirna Decreases C/ebp␣ Prosupporting
confidence: 90%
“…Thyroid transcription factor 1 (TTF1), a key transcription factor in type II cell development, did not increase in hyperoxia (Fig. 4A), consistent with a previous report (14). Furthermore, C/EBP␣ siRNA injection did not change TTF1 mRNA levels in hyperoxia.…”
Section: Intrapulmonary Delivery Of C/ebp␣ Sirna Decreases C/ebp␣ Prosupporting
confidence: 90%
“…If the same effect were present in the small airways, then it could be speculated that changes in Hip influence the thickness of the airway muscle layer and induce more or less airflow limitation. Secondly, a study of POGACH et al [35] demonstrated that several developmental pathways in the lungs of adult mice, including Hh, reactivate for tissue repair following hyperoxia. In addition, others have shown that embryogenic signalling pathways, such as Hh, are activated in human bronchial epithelial cells exposed to cigarette smoke [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ataxin 7 (Atxn7) coding for a relatively ubiquitous protein, is at the top of the list of upregulated genes. Members of the ataxin family have recently been linked to tissue regeneration and epithelial cell repair in several organs, including the skin (52). The gene for the 2d form of calcium-calmodulin-dependent kinase II (CaMKII2d), a strong inducer of cardiac hypertrophy (19), may control keratinocyte proliferation and differentiation, which are calciumdependent processes.…”
Section: Substantial Alterations In the Global Gene Expression Profilmentioning
confidence: 99%